Human Voice and Android Voice: A Comparative Study - Marek ZIMNAK (Communications of International Proceedings, 2020)
The idea of constructing androids using the human voice has become an element of the intensive development of artificial intelligence. Technological advances have made the android voice difficult to distinguish from the human voice. Such a situation may generate various dangers in the future. The author of the article prepared an experiment aimed at assessing how much people are able to judge the origin of the subject with whom they are in contact, based only on their voice. To this end, he presented samples of human voices and android voices for evaluation by participants in the experiment. Since both the ethical issues and the security issues of cooperation between the two species are not clearly articulated today, the results of this type of pilot study may have a practical dimension in the future in the context of social trust in artificial intelligence entities.
Keywords: Voice; Android; Artificial Intelligence (AI); Ethics.